Pesantren Intellectual Activism Outside of Islam and Muslims: Study of the Jalan Dakwah Pesantren (2016) Documentary Film - Qosim, Ahmad Afrizal; Nur Rahma, Istifadah (Kalijaga Journal of Communication, 2024)
This research tries to reexamine the meaning of Pesantren (Islamic boarding schools) as inclusive spaces by reinterpreting the film Jalan Dakwah Pesantren (2016). As a prophetic space born from a long process of Indonesian cultural and educational history, Pesantren is often attached simply as a label for traditional Islamic education and ignores its role outside of Islam, which also uses the Pesantren education model. This article strengthens the historical perspective of ​​ Pesantren as inclusive spaces that can be used and applied by people outside of Islam and Muslims in Indonesia and the world. This research uses an interdisciplinary approach (interdisciplinary studies), including literature reviews and in-depth interviews, by exploring relevant historical forms of Indonesian educational experience, starting from Hindu, Buddhist, and Kapitayan education to Islam in the Archipelago and then similar models in other parts of the world. This research shows that the normalization of Pesantren traditions as intellectual activism has been widely absorbed by cultural actors outside of Islam and Muslims as a basis for deepening character and insight. Pesantrens, as examples of education, have been in the position of cross-cultural institutions and carry out the mission of transmitting religious and cultural knowledge outside of Islam.